Highlighting Astyanax species diversity through DNA barcoding - Rossini, Bruno César (2016)
DNA barcoding has been used extensively to solve taxonomic questions and identify new species. Neotropical fishes are found in a wide variety of shapes and sizes, with a large number of species yet to be described, many of which are very difficult to identify. Characidae is the most species-rich family of the Characiformes, and many of its genera are affected by taxonomic uncertainties, including the widely-distributed, species-rich genus Astyanax. In this study, we present an extensive analysis of Astyanax covering almost its entire area of occurrence, based on DNA barcoding. The use of different approaches (ABGD, GMYC and BIN) to the clustering of the sequences revealed ample consistency in the results obtained by the initial cutoff value of 2% divergence for putative species in the Neighbor-Joining analysis using the Kimura-2-parameter model. The results indicate the existence of five Astyanax lineages. Some groups, such as that composed by the trans- Andean forms, are mostly composed of well-defined species, and in others a number of nominal species are clustered together, hampering the delimitation of species, which in many cases proved impossible. The results confirm the extreme complexity of the systematics of the genus Astyanax and show that DNA barcoding can be an useful tool to address these complexes questions.